Analisis Konsekuensi Pengunduran Diri Pekerja Profesional Dalam Perspektif Regulasi Ketenagakerjaan - Hendry Frand Tia; Sufiarina (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The working relationship between the employer and employee is an agreement between two parties. Laws that provide legal certainty for labor develop quite comprehensive and detailed for the protection of the labor if an employer terminates the employment agreement. The purpose of this writing is to explore the nature of the legal certainty of the parties (employers and workers) in the event of termination of employment by employees who work as a professional worker. The legal research used is normative juridical, with primary, secondary and tertiary legal materials. The results of the research found that many professional workers still take refuge in laws that are supposed to protect unskilled laborers, and these professional workers enjoy all the 'an sich' benefits of the Labor Law. If a company terminates the employment agreement with its employee, the written laws which contain various sanctions (including criminal sanctions) require the company to go through many stages, including payment of severance package. With the perspective of the principle of equality before the law, the author does not find any written laws regarding procedures and sanctions (penalties) for a professional worker who terminates the employment relationship unilaterally with the company.